Achieving and maintaining of short-cut nitrification in a cyclic activated sludge system - Shaopo, Wang (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
A lab-scale Cyclic Activated Sludge Technology (CAST) system was operated more than 5 months to evaluate the effects of the operation mode on nitrogen removal performance and investigate a feasible method for achieving short-cut nitrification in the system. Results showed that nitrogen was removed by conventional biological nitrification and denitrification in traditional operation mode (fill/aeration 2 h, settle 1 h, decant 1 h), whereas short-cut nitrification and denitrification was the main nitrogen removal pathway in modified operation mode and the nitrogen removal performance was enhanced. Short-cut nitrification was successfully achieved in CAST system at 17 ± 1 °C by adjusting operation conditions and the average total nitrogen removal efficiency increased by 11.4% compared to traditional mode. It was assumed that low dissolved oxygen (<1.0 mg/L) limitation combined with free ammonia (0.28-0.34 mg/L) inhibition on nitrite-oxidizing bacteria caused nitrite accumulation in modified mode. During maintaining period of short-cut nitrification, preset aeration time enhanced ammonium-oxidizing bacteria dominance. It was also found that low DO could result in overgrowth of filamentous microorganisms and poor sludge settleability. The pH variation could provide effective information for controlling aeration duration in modified mode. However, no evident breakpoint appeared on pH and DO profiles in traditional mode